Effect of 2, 2, 6, 6-Tetramethylpiperidinyl-Oxide (TEMPO) as an Electrolyte Additive and its SEI Formation on MCMB-Electrode. (25th June 2020) - Lin, Shawn D.; Yohannes, Yonas Beyene; Hwang, Bing-Joe; Wu, Nae-Lih
Abstract : In this study, we developed the benefit of TEMPO additive for the suppression of the solvent/additive decomposition by trapping the radicals formed. With unusual stability as a neutral radical the 2 % TEMPO as an additive into STD + 5% FEC electrolyte resulted in the modification of the interphase. Through in-situ DRIFTS results we can find out and investigate the mechanism for the decomposition of TEMPO. The studies described herein also demonstrate that MCMB-electrodes in STD + 5% FEC solution containing TEMPO additive can be utilized together with high voltage cathode.